Letter (copy) - Rickard, Mildred
1938-12-21 038-0113-002 COPY 15 Hurst View Road, South Croydon. 21. 12. 38. Dear Miss Sutherland, The Superintendent of the Basque Children's Gome [Home] at Lancing has written to me that she has received no money for our Basque ward, Begona Gutieves, for some time, and as we have paid up to December 26th, and you have sent me a receipt for that amount, I can't understant [understand] it. I will await your reply before answering her letter, but wonder if it would be easier for your office if I sent the money direct to Lancing each month and just sent the surplus on to you for the general fund. Sincerely yours, (Signed) MILDRED RICKARD Macfarlane Edinburgh 292/946/38/113(II)